A255 HOSPITALIZATIONS FOR VENOUS THROMBOEMBOLISM ARE INCREASED IN PATIENTS WITH ELDERLY-ONSET INFLAMMATORY BOWEL DISEASE: A POPULATION-BASED MATCHED COHORT STUDY. (15th March 2019) - Kuenzig, E; McCurdy, J; Murthy, S; Stukel, T A; Nguyen, G C; Kaplan, G G; Talarico, R; Benchimol, E I
Abstract: Background: Inflammatory bowel disease (IBD) is becoming increasingly common among elderly Canadians. The risk of venous thromboembolism (VTE) in IBD patients increases with age. Aims: Compare the incidence of VTE-associated hospitalizations in patients with elderly-onset IBD and non-IBD controls. Methods: Incident cases of elderly-onset IBD (≥65y) diagnosed between April 1, 2002 and March 31, 2014 were identified from health administrative data in Ontario using a validated algorithm. Cases were age- and sex-matched to five non-IBD controls. Hospitalizations for VTE were identified from the CIHI Discharge Abstract Database. VTE was defined as deep venous thrombosis (DVT) and/or pulmonary embolism (PE) and could either be the reason for hospitalization or a complication occurring during hospitalization for another reason. The cumulative 5-year risks of VTE, DVT, and PE were calculated for cases and controls. The incidence of VTE, DVT, and PE were compared in cases and controls using a negative binomial model adjusting for comorbidities, rural/urban residence, and income. Results are presented as incidence rate ratios (IRR) and 95% confidence intervals (CI). Analyses were conducted for all types of IBD combined and separately for Crohn's disease (CD) and ulcerative colitis (UC). We additionally compared the risk of VTE by type of IBD, adjusting for age, sex, comorbidities, rural/urban residence, and income. Results: The 5-year risk of VTE was 5.3% in cases compared to 0.56% in controls (IRR 5.78, 95% CI 4.58–7.30). The incidence of DVT (IRR 7.45, 95% CI 5.38–10.32) and PE (IRR 4.76, 95% CI 3.55–6.39) were similarly increased in IBD. The association persisted when stratifying by disease type (Table). VTE was significantly more common in patients with CD than UC (IRR 1.36, 95% CI 1.03–1.81). DVT and PE were slightly, but not significantly, more common in CD than UC (DVT: IRR 1.35, 95% CI 0.93–1.96; PE: IRR 1.44, 95% CI 0.99–2.08). Conclusions: Elderly patients with IBD are significantly more likely to develop a VTE than people without IBD. Gastroenterologists treating these patients should be aware of the increased risk and future research should seek to identify predictive factors for VTE so that physicians can treat patients with prophylactic measures, when appropriate. Funding Agencies: CAG, CCC, CIHR